PENGARUH SERVICE QUALITY TERHADAP SATISFACTION DAN CUSTOMER LOYALTY KOPERASI DADIRAH DI DILI TIMOR-LESTE - Pereira, Daniel; Giantari, I Gusti Ketut; Sukaatmadja, I Putu Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Service  quality is an attitude and behavior of people in providing services according to the needs, desires and expectations of consumers being served.  A better service quality able to increase satisfaction and customer loyalty. This study aims to analyze the influence of service quality towards customer satisfaction and loyalty. This research was conducted  in  Cooperative  of  Dadirah, using 64 members of cooperative as a sample. Data were collected by conducting interviews and questionnaires. Subsequently collected data were analyzed using descriptive analysis and Partial Least Square. The results of this study shows that service quality which is given by cooperativa of Dadirah  have positive and significant effect towards customer satisfaction and loyalty,  but the satisfaction is found not significant positive effect on customer loyalty. The implications of this study indicate that the service quality plays an important role in creating customer satisfaction and customer loyalty.
Keywords: service quality, customer satisfaction, and customer loyalty